Review article: Blockchain as an innovative solution for halal verification of food products in global supply chains - Fitriani, Nira Nur; Eliza, Zulfa (Journal of Halal Science and Research, 2025)
Blockchain technology is an innovative solution to improve transparency, traceability, and security in the halal supply chain. With its decentralized and immutable nature, blockchain enables end-to-end product tracking, increasing consumer confidence in the halalness of products. The purpose of this paper is to discuss the concept of blockchain, its implementation in halal verification, advantages such as efficiency and data security, and challenges faced. The research method used is a literature review with a qualitative and explanatory approach, utilizing primary and secondary sources through a literature study. Data was analyzed through stages of data display, data reduction, and conclusion verification, making this study observational in nature to describe and analyze practices and challenges in blockchain adoption for halal verification. The results show that blockchain has great potential to address the issue of uncertainty and improve compliance with halal standards, but requires collaborative efforts from all stakeholders to overcome challenges in its implementation. The conclusion highlights that blockchain integration in the halal supply chain can significantly enhance transparency, traceability, and security, minimize fraud, and increase consumer trust. However, barriers such as high costs, technological complexity, regulatory limitations, and industry resistance must be addressed. With further development and collaboration, blockchain has the potential to become a key solution in ensuring the integrity and sustainability of the global halal supply chain. Keywords: Blockchain technology, Halal certification, Halal supply chain, Smart contracts, Transparency, Traceability.